Asymmetric [3+2] Cycloaddition of Azomethine Ylides Catalyzed by Silver(I) Triflate with a Chiral Bipyrrolidine-Derived Phosphine Ligand - Gu, Xin; Xu, Zhen-Jiang; Lo, Vanessa Kar-Yan; Che, Chi-Ming (Synthesis, 2012)
Two novel chiral bipyrrolidine-derived phosphine ligands L1 and L2 were synthesized. The ‘AgOTf + L1’ protocol catalyzes the asymmetric [3+2] cycloaddition of azomethine ylides with alkenes to give highly substituted pyrrolidines in good yields (up to 90%) with moderate to high diastereoselectivities (up to >19:1 dr) and enantioselectivities (up to 76%).
Keywords: asymmetric [3+2] cycloaddition; silver catalysis; azomethine ylides; chiral phosphine ligand; highly substituted pyrrolines